SEJARAH PERKEMBANGAN PONDOK PESANTREN SYAFA’ATURRASUL DALAM MEMAJUKAN PENDIDIKAN DI TELUK KUANTAN KABUPATEN KUANTAN SINGINGI (1988-2015) - Turisno, Turisno; Isjoni, Isjoni; Bunari, Bunari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: History is the knowledge of events and events that actually happened in the past in the life of society. The establishment of pesantren as a modern educational institution that upholds ketradisionalan society, is an important historical event. The purpose of this research are: (1) To know the process of establishment of boarding school Syafa'aturrasul. (2) To know the driving factor and the establishment of Islamic boarding school of Syafa'aturrasul. (3) To know the development of Islamic boarding school of Syafa'aturrasul from 1988-2015. (4) To find out how the public response to Pondok Pesantren Syafa'aturrasul. The result and discussion was the Pondok Pesantren Syafa'aturrasul on 27 December 1988. The establishment of Pondok Pesantren Syafa'aturrasul in line with the needs and ideals of the noble nation of Indonesia, especially Kuantan Singingi Regency which was pioneered by H. Amazone YS and H. Ir. Ahmiyul Ra'uf who had the idea to form an Institution of Pondok Pesantren. The educational institution aims to educate the reliable human resources for the santri who will become useful for the nation and the nation. In the establishment of this pesantren cottage must have a driving factor and its obstacles, among others is the encouragement of society to the establishment of this pesantren hut while the inhibitor is one of them is in the field of finance. The development of pesantren is very rapidly from year to year, both in terms of facilities and infrastructure. Pondok Pesantren also has a response from the community, the community is very supportive and encouraging towards the establishment of this pesantren cottage. The establishment of Pondok Pesantren Syafa'aturrasul in line with the needs and ideals of the noble nation of Indonesia, especially Kuantan Singingi Regency which was pioneered by H. Amazone YS and H. Ir. Ahmiyul Ra'uf who had the idea to form an Institution of Pondok Pesantren. The educational institution aims to educate the reliable human resources for the santri who will become useful for the nation and the nation. at the beginning of the establishment has 8 students or students by using the mosque as a place of teaching and learning process. And do not have dorms and facilities are limited.Keyword: History of Development of Islamic Boarding School Syafa'aturrasul